2022
DOI: 10.3390/ijms23073617
|View full text |Cite
|
Sign up to set email alerts
|

TRPV2: A Key Player in Myelination Disorders of the Central Nervous System

Abstract: Transient potential receptor vanilloid 2 (TRPV2) is widely expressed through the nervous system and specifically found in neuronal subpopulations and some glial cells. TRPV2 is known to be sensitized by methionine oxidation, which results from inflammation. Here we aim to characterize the expression and regulation of TRPV2 in myelination pathologies, such as hypomyelination and demyelination. We validated the interaction between TRPV2 and its putative interactor Opalin, an oligodendrocyte marker, in mixed glia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Studies have shown TRPV2 regulation during inflammation in microglia and immune cells, as well as during remyelination in oligodendrocytes. TRPV2 has been suggested as an interesting clinical target for the development of therapeutic interventions for myelination disorders[48]. GSTM3 colocalizes with amyloid-beta plaques in AD and reduces antioxidant defense.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown TRPV2 regulation during inflammation in microglia and immune cells, as well as during remyelination in oligodendrocytes. TRPV2 has been suggested as an interesting clinical target for the development of therapeutic interventions for myelination disorders[48]. GSTM3 colocalizes with amyloid-beta plaques in AD and reduces antioxidant defense.…”
Section: Resultsmentioning
confidence: 99%
“…The findings suggest that TRPV2 may play a key role in myelination and could be an interesting clinical target for the treatment of demyelinating diseases (Ref. 55).…”
Section: Trp and Autoimmune Diseasesmentioning
confidence: 98%
“…Recently, mechanosensitive (MS) ion channels have come to the forefront of neuromechanobiology and have been shown to undergo activation or differential expression in response to mechanical stimuli within the CNS, [32] with important functions in blood-brain barrier maintenance, [33] neural differentiation, [34,35] nociception, [36][37][38] neural-glia communication, [39] and glia activation. [40][41][42][43][44][45] Critically, MS channel expression is perturbed in neurodegenerative disorders [46] including Alzheimer's disease, [45,47] myelination disorders, [48][49][50] migraine, [51][52][53] and glioma. [54][55][56] In order to gain insight into the role of cyclic mechanical forces in the onset and evolution of peri-electrode gliosis, recent studies have described the development of cell culture models, which mimic physiologically relevant neuroelectrode micromotions and which have demonstrated partial success in reproducing the processes of gliosis in vitro.…”
Section: Introductionmentioning
confidence: 99%